The Impact of Transformational Leadership Style and Compensation on Teacher Performance at Madrasah Aliyah - Muhammad Sehol (AL-ISHLAH: Jurnal Pendidikan, 2022)
Building a motivating environment can be an organization's most significant challenge because a motivated, satisfied, and committed workforce is harder to find and create. It keeps leaders in an organization evaluating, experimenting, and adapting to different people, including their behaviours, attitudes, personalities and cultures, traditions, habits, and experiences. This study aims to determine and analyze the effect of transformational leadership style and compensation on teacher performance through work motivation at a private madrasah Aliyah in Buru Regency. The descriptive and verification method with a quantitative research approach is used—sampling using the purposive sampling technique, with a sample of 41 teachers. Sources of data used in the study are primary data and secondary data. The study's results indicate that transformational leadership influences work motivation and teacher performance. Likewise, compensation directly influences the motivation and performance of Madrasah Aliyah Alhilaal Namlea Buru Regency teachers. The results of the Sobel test calculator calculation show an indirect effect of transformational leadership on teacher performance through work motivation. Likewise, compensation also has an indirect impact on teacher performance through work motivation. So it can be concluded that work motivation can mediate the relationship between balance and teacher performance at Madrasah Aliyah inBuru Regency. The results of this study can also be used for researchers and further researchers as well as parties who need it as a source of reference and valuable information in adding to the reader's insight